Using point-of-care HbA1c to facilitate the identification of diabetes and abnormal glucose regulation in primary healthcare settings - Pi, Linhua; Zheng, Ying; Shi, Xiajie; Wang, Zhen; Zhou, Zhiguang (Frontiers in Public Health, 2023)
Background Glycated hemoglobin A1c (HbA1c) is a critical index for the diagnosis and glycemic control evaluation of diabetes. However, a standardized method for HbA1c measurement is unaffordable and unavailable among the Chinese population in low-resource rural settings. Point-of-care (POC) HbA1c testing is convenient and inexpensive, but its performance remains to be elucidated. Objective To investigate the value of POC HbA1c for identifying diabetes and abnormal glucose regulation (AGR) in the resource-limited Chinese population. Methods Participants were recruited from 6 Township Health Centers in Hunan Province. Samples for POC HbA1c, venous HbA1c, fasting plasma glucose, and 2 h-plasma glucose were obtained after physical examination. The oral glucose tolerance test was performed as the gold standard for diagnosis. The diagnostic capacities of the POC HbA1c measurement in predicting undiagnosed diabetes and AGR were evaluated. Results Among 388 participants, 274 (70.6%) normoglycemic controls, 63 (16.2%) prediabetes patients, and 51 (13.1%) diabetes patients were identified with oral glucose tolerance test (OGTT). Meanwhile, among 97 participants who underwent two HbA1c detection methods simultaneously, a positive correlation was found between POC HbA1c and standardized HbA1c (r = 0.75, P < 0.001). No notable systematic difference was observed from the Bland-Altman Plots. The POC HbA1c cutoff values were 5.95 and 5.25%, which efficiently identified diabetes (AUC 0.92) and AGR (AUC 0.89), respectively. Conclusions The alternative POC HbA1c test efficiently discriminated AGR and diabetes from normoglycemia, especially among the Chinese population in primary healthcare settings.